2003
DOI: 10.1034/j.1600-051x.2003.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival plaque removal in buccal and lingual sites using a novel low abrasive air‐polishing powder

Abstract: The novel low abrasive air-polishing powder is superior to curettes in removing subgingival plaque from pockets of 3-5 mm depth in supportive periodontal therapy and offers greater patient comfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
154
0
27

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(188 citation statements)
references
References 29 publications
7
154
0
27
Order By: Relevance
“…2.A). Recent studies have shown that glycine-based powders have lower abrasiveness compared to other bicarbonatebased prophy-powders (32,36). Indeed, this type of softer prophy-powder has been developed to be safely applied subgingivally during supra-and subgingival deplaquing (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2.A). Recent studies have shown that glycine-based powders have lower abrasiveness compared to other bicarbonatebased prophy-powders (32,36). Indeed, this type of softer prophy-powder has been developed to be safely applied subgingivally during supra-and subgingival deplaquing (17).…”
Section: Discussionmentioning
confidence: 99%
“…The prophy-powder commonly used with air-polishing systems is sodium bicarbonate (NaHCO 3 ) with particle dimensions in the range of 100 -200 μm (14,15). Recently, an amino-acid-glycine powder has been thought to be of help in periodontal treatment as well as for air-polishing (17,32,33). Whereas, "bioactive glass" prophy-powder constituted by calcium sodium phosphosilicate has been proposed for therapeutic and bioactive air-polishing procedures due to its capacity to react with saliva and deposit hydroxycarbonate apatite (HCA) (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Uç kökün uzun aksına 60-90 derece açı ile yönlendirilerek supra ve subgingival biyofilm uzaklaştırılır. Bu yöntemle yapılan biyofilm eliminasyonu sırasında sement ve dentin dokularında oluşabilecek hasar minimuma indirgenir 40 ve restoratif dental materyallerin bulunduğu bölge-lerde de güvenle kullanılabilir.…”
Section: Ultrasonik Ve Sonik Aletlerle Yapılan Diş Taşı Temizliği Ve unclassified
“…Air polishing cihazında kullanılan glisin, implant yüzeyine sodyum bikarbonattan daha az zarar verdiği, temizlik sonrası rekolonizasyon oluşumunu 24 saat inhibe ettiği gösterilmiştir 47 50 . Bazı araştırmalarda sodyum bikarbonat ile yapılan supragingival air polishing sonucu anfizem oluşabildiği bildirilmiş 51,52 oysa glisin uygulaması sonucu anfizem oluşumuna rastlanmamıştır 40,50,53 . Demineralize olmamış mine dokusu üzerine zararlı etkisi olmadığı gösterilmiş olmasına rağmen uygulamada yapılabilecek yanlışlıklar diş ve çevre dokularda hasara neden olabileceği bildirilmiştir 54 .…”
Section: Ultrasonik Ve Sonik Aletlerle Yapılan Diş Taşı Temizliği Ve unclassified
See 1 more Smart Citation